Come la Chimica toscana si prostrò di fronte al fascismo: Il caso di Piero Ginori Conti - Fontani, Marco; Costa, Mariagrazia (Chimica nella Scuola, 2022)
The purpose of the present work is to arouse interest, in learning more about the Tuscan Chemical Industry. The small Tuscan community could rely on a limited number of industrialists; one these few was Piero Ginori Conti (1865 - 1939), prince of Trevignano. He was the key driver in revival of the Larderello industrial activity in the chemical and energy field. The present work tries to throw light on what may have gone wrong with Prince Piero Ginori Conti’s economical politics during those years when in Italy the dictatorship struggled to establish and later, when the whole Nation was subjugated to fascism.